Kajian Eksperimental Dan Simulasi Numerik Penggunaan Fiberglass Sebagai Bahan Serat Pada Balok Beton - Sunarwadi, Hadi Surya Wibawanto; Kartika, Deviany; Erfan, Muhammad; Dermawan, Adi Susetyo (Jurnal Ilmiah Teknik Sipil; Vol 27 No 1 (2023): Jurnal Ilmiah Teknik Sipil, Vol. 27 No. 1, Maret 2023DO - 10.24843/JITS.2023.v27.i01.p05, 2023)
Construction of reinforced concrete beams requires resistant material with good deformability. Concrete is a material that is strong in compression but weak in tension. So, this research is to use fiberglass as a fiber in concrete to strengthen the tensile strength of the concrete. The results of the initial research found that the compressive strength capacity of concrete with the use of fiberglass increased to 27% compared to plain concrete without fiber. Meanwhile, if we look at the tensile capacity of concrete, it shows that there is an increase of 32% compared to plain concrete without fiber. Then from the numerical simulation results it was found that the use of fiberglass in the construction of flexible beams can minimize deflection by 12%, reduce the maximum compressive stress by 0.04%, and the maximum tensile stress by 0.71%.